Kajian Perbandingan Kenyamanan Ruang Desain Interior Kafe yang Instagramable di Surabaya (Studi Kasus: Carpentier Kitchen dan Threelogy Coffee) - Albertus Adi Putra; Adi Santosa; Poppy Firtatwentyna Nilasari (Intra, 2019)
This research was conducted to determine the level of comfort of a café room with an instagramable interior design using Carpentier Kitchen with Threelogy Coffee as a case study. The emergence of cafes with Instagramable interior design made researchers interested in conducting research to determine the level of comfort of the cafes' spaces. The analysis technique used in this study is triangulation of data sources by using people as data to help determine the comfort level of the space from the café case studies used. The results show that Threelogy Coffee has a slightly better level of room comfort than Carpentier Kitchen.